2005
DOI: 10.1007/bf03219008
|View full text |Cite
|
Sign up to set email alerts
|

Allyloxy- and benzyloxy-substituted pyridine-bis-imine iron(II) and cobalt(II) complexes for ethylene polymerization

Abstract: A series of ethylene polymerization catalysts based on tridentate bis-imine ligands coordinated to iron and cobalt was reported. The ligands were prepared through the condensation of sterically bulky anilines with allyloxy-and benzyloxy-substituted 2,6-acetylpyridines. The pre-catalyst complexes were penta-coordinate species of the general formula {[(ArN=C(Me)) 2 (4-RO-C 5 H 3 N)]MCl 2 } (Ar=ortho dialkyl-substituted aryl ring; R=allyl, benzyl; M=Fe, Co). In the presence of ethylene and methyl alumoxane cocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In comparison with the iron complexes, cobalt complexes are less active at ethylene polymerization (about an order of magnitude) and produce polyethylene (PE) with lower molecular weight (MW). [9][10][11][12][13] Homogeneous catalysts based on LFeCl 2 complexes produce PE with a broad molecular weight distribution (MWD). [5,8,9,13] The values of polydispersity depend on the polymerization conditions, structure of ligand, and nature of activator; but in all cases, the M w =M n values noticeably exceed 2, indicating that a set of different active centers forms in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the iron complexes, cobalt complexes are less active at ethylene polymerization (about an order of magnitude) and produce polyethylene (PE) with lower molecular weight (MW). [9][10][11][12][13] Homogeneous catalysts based on LFeCl 2 complexes produce PE with a broad molecular weight distribution (MWD). [5,8,9,13] The values of polydispersity depend on the polymerization conditions, structure of ligand, and nature of activator; but in all cases, the M w =M n values noticeably exceed 2, indicating that a set of different active centers forms in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, the bulk of the substituents in the aryl rings of the bis(imino)pyridine ligand of cobalt complexes exerts a pronounced effect on their polymerization activity and on the M w characteristics of the produced polyethylene [11,[14][15][16][17]. Using polymerization quenching with radioactive carbon monoxide ( 14 CO), we determined the C P and k P values for the ethylene polymerization over 2-t BuLCoCl 2 and 2,5-t Bu 2 LCoCl 2 with MAO as an activator.…”
Section: Effect Of Substituents In the Aryl Rings Of The Ligand On Thmentioning
confidence: 99%
“…It was found by 1 H NMR spectroscopy [9,[12][13][14] that the addition of the ethylene to the catalytic systems L'Co(II)Cl 2 + MAO and L'Co(II)Cl 2 + AlMe 3 (L' = 2,6-Me 2 L, 2,4,6-Me 3 L, 2,6-i Pr 2 L, 2-t BuL) results in a rapid reduction of the initially formed complexes of cobalt(II) to cobalt(I) species and formation of the only one type of the intermediate with close structure both with MAO and AlMe 3 activators, determining the single-site character of these catalysts and close catalytic properties. For bis(imino)pyridine cobalt complexes it was shown that the substituents in the o-position of the aryl rings of the ligand have a pronounced effect upon the MW-characteristics of the resulting polymer [11,[14][15][16][17]. Complexes bearing more bulky substituents ( i Pr, t Bu) produce PE with a noticeably higher MW in comparison with the corresponding Me-substituted complex.…”
Section: Introductionmentioning
confidence: 97%